2017
DOI: 10.2495/sdp-v12-n5-908-921
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a urban sustainability and life quality index for elderly

Abstract: The research here presented originates from some of the ongoing challenges of our society: the demographic changes and the high share of population living in urban areas. The aim of the research is the definition of an index of sustainability and quality of life for elderly at suburban scale, not only able to outline aspects related to the local territorial context but also to represent the neighbourhood level. This would provide significant added value to existing indicators that represent the quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A hybrid strategy, that uses both objective and subjective methods, with quantitative and qualitative analysis should be preferred (Huxley et al, 2012). Tools such as the "Assessment of Urban Sustainability" (Astiaso Garcia et al, 2017), the "Universal Design-based Framework" (Mosca and Capolongo, 2020), the "MASBE tool" (Mercader-Moyano et al, 2020), the "DIETool" (Rebernik et al, 2020), and the "Social Sustainability Indicators" (Olukoya and Atanda, 2020) are recent examples of tools that use a combination of objective and subjective methods. As a result, several tools dealt with accessibility, however, only a few recent works presented features about inclusion, and more broadly about equity and diversity.…”
Section: Resultsmentioning
confidence: 99%
“…A hybrid strategy, that uses both objective and subjective methods, with quantitative and qualitative analysis should be preferred (Huxley et al, 2012). Tools such as the "Assessment of Urban Sustainability" (Astiaso Garcia et al, 2017), the "Universal Design-based Framework" (Mosca and Capolongo, 2020), the "MASBE tool" (Mercader-Moyano et al, 2020), the "DIETool" (Rebernik et al, 2020), and the "Social Sustainability Indicators" (Olukoya and Atanda, 2020) are recent examples of tools that use a combination of objective and subjective methods. As a result, several tools dealt with accessibility, however, only a few recent works presented features about inclusion, and more broadly about equity and diversity.…”
Section: Resultsmentioning
confidence: 99%
“…On a wider territorial scale, the fundamental role of cities is widely recognized in the literature; in [31] it was found that on an urban scale, problems can be tackled more effectively by the easier communication with local decision makers; in [32][33][34] the problem of energy self-sufficiency at municipal level was addressed, identifying solutions to increase the RES share on the electricity consumption; in [35] the possibility of using municipal waste was evaluated, for building envelopes for nZEB; in [36] a methodology was proposed for the preparation of an urban action plan based on carbon footprint assessment related to a city in southern Italy; in other works, the field of study was more limited and reached the neighbourhood scale [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The larger houses with greater frequency are isolated. They have larger dispersing surfaces and, subsequently, heat losses [61].…”
Section: Description Of Dwellings and Energy Consumption Analysismentioning
confidence: 99%